Rasch Career Self Efficacy Scale Analysis for High School Students - Ni Luh Made Wia Dwiarya Putri; Kadek Suranata; Luh Putu Sri Lestari (Bisma The Journal of Counseling, 2021)
Career self-efficacy is one of the important factors that determine the success of students in carrying out their careers. Likewise with school counselors, measuring students' career self-efficacy will help them understand and develop strategies to develop students' career plans. For this reason, a valid and reliable career efficacy measurement tool is needed. This study aims to analyze the feasibility of student career success scale based on RASCH modeling. Participants in this study were 30 students who were involved as respondents in a 25-item career self-efficacy test. Rasch analysis was made by the WINSTEPS 3.73 program to evaluate the Indonesian version of the career self-efficacy scale by looking at the validity and reality of the item-person fit measure, Cronbach's alpha value, item-person separation index, dimensions, response patterns in the scalogram, and bias items according to gender. The results of this study indicate that of the 25 items there are 5 items that are out of fit or do not meet the RASCH measurement model. The reliability of the Cronbach Alpha scale is 0.96 or very high. The total gross variance described by the measure is 47%, which means this scale is able to predict students' career self-efficacy quite accurately. Overall, it can be concluded that the Indonesian version of the student career self-efficacy scale has good psychometric properties so that it can be used for assessment and research.